Gap Analysis of The National Objectives Islamic Religious Education In The Spiritual Emotional And Intellectual Domains at MTs Ishlahul Masalik - Laily Farihatul Izza; Novita Dwi Astuti (Sunan Kalijaga International Journal on Islamic Educational Research, 2025)
This study aims to analyze the gap between the national objectives of Islamic Religious Education (PAI), as mandated in Law No. 20 of 2003 concerning the National Education System, and the reality of PAI learning at MTs Ishlahul Masalik Tebluru, Solokuro District, Lamongan Regency. The study focuses on three domains of educational achievement: spiritual, emotional, and intellectual. The main argument of this study is that the national objectives of PAI have not been fully realized in classroom practice, particularly in transforming religious knowledge into students’ awareness, attitudes, and reflective thinking. This study employed a descriptive qualitative approach. The research subjects were students from grades VII–IX, while the key informants were PAI teachers and the head of the madrasah. Data were collected through participatory observation, semi-structured interviews, document analysis, and field notes. The data were analyzed descriptively through the stages of data reduction, data display, and conclusion drawing. The findings show that in the spiritual domain, students are able to memorize prayers and the basic principles of worship, but their religious practice remains limited and their spiritual awareness is relatively low. In the emotional domain, students understand the concepts of morality, discipline, and empathy, yet their daily behavior is not consistently aligned with the values taught. In the intellectual domain, students master PAI materials mainly through memorization, but their critical, reflective, and applicative thinking skills remain weak. This study implies that PAI learning needs to move beyond cognitive memorization toward integrated learning that strengthens spiritual awareness, emotional character, and higher-order thinking skills. However, as a qualitative case study, the findings are context-specific and cannot be generalized to all madrasahs without further comparative research.